A nose for negotiation - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
How can ACP countries participate most effectively in the world s highly complex agricultural negotiations? What strategies in information and communication could help? What barriers need removing, what bridges need building?The questions will be...